Krmiljenje temperature hladilne vode motorja z notranjim zgorevanjem v preskuševališču - Bombek, Gorazd (Strojniški vestnik, 2001)
The solution to an engine-cooling problem, which occured during the testing of a water-cooled internal combustion engine in a test stand for air-cooled internal combustion engines, is presented in this article. A water-to-water heat exchanger and a control valve were incorporated into an existing engine-cooling system. The cooling-water temperature was controled with a computer, which was also used for the date acquisition. The system was tested in the laboratory and allows to set the cooling-water temperature regardless of the operating regime of the engine.
Keywords: motorji ZNZ; hlajenje motorjev; voda hladilna; regulacija temperature; motorji z notranjim zgorevanjem; hlajenje; toplotni menjalniki; regulacija